Effects of aromatherapy by Rosaceous on the severity and systemic symptoms of primary dysmenorrhea - Ataollahi, Maryam; Ali Akbari, Sedigheh; Mojab, Faraz; Roshanaie, Ghodratollah (Advances in Nursing & Midwifery, 2016)
Background and Aim: Dysmenorrhea, defined as pain associated with menstruation that affects millions of women in the reproductive age worldwide. Considering the high prevalence of dysmenorrhea and its adverse consequences on quality of life, the present study examined the effects of Rosaceous on the severity of primary dysmenorrhea and its systemic manifestations. Materials and Methods: This double blind clinical trial was performed on 110 students of Hamadan University of Medical Sciences. Students randomly assigned into intervention and control groups. Both groups were matched before intervention for age, education level, BMI, income, education wife, age of menarche and marital status. In the intervention group in the first 3 days of menstruation, 10 drops of Rosaceous extract were given to the subjects two times daily for two consecutive menstrual cycles. The controls take placebo. Severity of primary dysmenorrhea is compared in the two groups using the paired t test and between groups using the independent t test. Findings: The severity of primary dysmenorrhea and systemic manifestations decreased in both groups, this reduction was more significant in the Rosaceous group (p <0.001). Conclusions: The results of this study results showed a positive impact of Rosaceous in reduction of severity of primary dysmenorrhea and systemic manifestations. It seems that can be used to reduce the severity of primary dysmenorrhea and systemic manifestations. Keywords: Dysmenorrhea; Rosaceous; Traditional Medicine.